RAPPER, Rapid Assessment of PeriPhyton Ecology in Rivers, evaluation of RAPPER as a rapid assessment method, and as a complement to diatom-based assessments. (March 2015) - Kelly, Martyn; Krokowski, Jan
No abstract available